2005
DOI: 10.1083/jcb.200412169
|View full text |Cite
|
Sign up to set email alerts
|

Deep-etch EM reveals that the early poxvirus envelope is a single membrane bilayer stabilized by a geodetic “honeycomb” surface coat

Abstract: Three-dimensional “deep-etch” electron microscopy (DEEM) resolves a longstanding controversy concerning poxvirus morphogenesis. By avoiding fixative-induced membrane distortions that confounded earlier studies, DEEM shows that the primary poxvirus envelope is a single membrane bilayer coated on its external surface by a continuous honeycomb lattice. Freeze fracture of quick-frozen poxvirus-infected cells further shows that there is only one fracture plane through this primary envelope, confirming that it consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
137
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 135 publications
(169 reference statements)
13
137
0
Order By: Relevance
“…This antibody (Hu anti-VACV Ab) originated from an individual who had been vaccinated five times against smallpox and contained 52% of anti-IMV and 3% of anti-EEV activity compared with Rb anti-VACV Ab (43). The results demonstrated the benefit of HP in combination with human antibody (versus Hu anti-VACV Ab alone; P Ͻ 0.05 for weight loss and signs of illness, days [4][5][6][7][8][9][10]. This suggested that PAs may be used in conjunction with vaccinia-immune globulin in treating smallpox and vaccinerelated complications.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This antibody (Hu anti-VACV Ab) originated from an individual who had been vaccinated five times against smallpox and contained 52% of anti-IMV and 3% of anti-EEV activity compared with Rb anti-VACV Ab (43). The results demonstrated the benefit of HP in combination with human antibody (versus Hu anti-VACV Ab alone; P Ͻ 0.05 for weight loss and signs of illness, days [4][5][6][7][8][9][10]. This suggested that PAs may be used in conjunction with vaccinia-immune globulin in treating smallpox and vaccinerelated complications.…”
Section: Resultsmentioning
confidence: 95%
“…IMV is surrounded by one lipid membrane (5)(6)(7)(8)(9) and is physically robust to aid virus transmission between hosts. CEV and EEV are IMV particles wrapped with an additional membrane derived from the trans-Golgi network (10) or endosomes (11) and are responsible for virus dissemination within the host (4).…”
mentioning
confidence: 99%
“…Moreover, ER, ERGIC, or Golgi proteins were not detected in the crescent membranes, and continuity between the latter and cytoplasmic tubules has been disputed (2,3). Similarly controversial is the nature of the IV and MV membranes, specifically whether they are composed of one (1)(2)(3)14) or two (8,15,16) sets of lipoprotein bilayers.…”
mentioning
confidence: 99%
“…The inability to discern clear continuity of the viral crescent membrane with a cellular organelle (4,7,8,10) led to speculation that the viral membrane is formed by a novel mechanism. Skepticism regarding de novo membrane formation, however, inspired efforts to obtain evidence for the origin of the IV membrane from a component of the cellular secretory pathway.…”
Section: Assembly Of Vaccinia Virus (Vacv) and Other Poxvirusesmentioning
confidence: 99%
“…begins with the formation of a crescent-shaped membrane that enlarges into a spherical immature virion (IV), which then condenses into a brick-shaped infectious mature virion (MV) (3,4,8). The MV consists of a core, containing the DNA genome as well as RNA polymerase and transcription factors, surrounded by a lipid membrane with more than 20 proteins, none of which are glycosylated.…”
Section: Assembly Of Vaccinia Virus (Vacv) and Other Poxvirusesmentioning
confidence: 99%